Amandemen Pasal 9 Konstitusi Jepang: Mungkinkah Berhasil Dilakukan? - Wendy Andhika (Jurnal Hubungan Internasional, 2013)
Japan effort made amendments to Article 9 of the constitution is strong enough to signal a change in perceptions and paradigms of the country in positioning itself and in seeing the outside world. If the amendments successful, it will change the architecture of Japan foreign policy which has been passive becoming more aggressive. It will impact to political constellation and polarization around. However, this paper wants to show Japan government domestically finds many obstacles. The obstacles center on a Japanese desire which not enthusiast to the amendment process in military issues and asked the leader of Japan to focus on humanity issues.